Trends and Patterns in Outpatients Visits Among Children and Adolescents in a Psychiatric Specialist Hospital, 2019–2023 - Wenjie Gu; Qing Zhao; Zhen Wang (Mental Health Science, 2026)
ABSTRACT Mental health problems burden children and adolescents globally, and the COVID‐19 pandemic has exacerbated these challenges, altering their healthcare‐seeking behaviors and mental health diagnostic patterns. However, few studies have systematically analyzed long‐term outpatient visit trends and diagnostic changes pre‐ and post‐pandemic, especially considering age and gender differences. Retrospective data of 74,779 valid pediatric (0–18 years) mental health outpatient visits (2019–2023) from Shanghai Mental Health Center were analyzed. Interrupted time series (ITS) analysis quantified COVID‐19 intervention impacts, with multiple logistic regression for associated factors. Pediatric mental health visits increased annually (2019–2023) except for a 2022 decline. Male visits were barely affected by pandemic interventions, while female visits (10–13 and 14–18 years) were significantly impacted, with COVID‐19 exerting short‐ and long‐term effects on 14–18‐year‐olds. Depressive episode (F32), hyperkinetic disorders (F90), and other anxiety disorders (F41) remained top three diagnoses, with two childhood‐specific emotional/behavioral disorders rising in proportion. The study confirms an upward trend in pediatric mental health visits with notable age‐gender differences, and targeted pandemic impacts on adolescent females. It highlights the urgent need for age‐ and gender‐specific mental health services, providing a reference for public health responses to pediatric mental health crises.